Using formative evaluation of a community-based opioid overdose prevention program to inform strategic communication for adoption, implementation, and sustainability - Candice Bangham; Stacey Cunnington; Sarah Fielman; Meredith Hurley; Sarko Gergerian; Jacey A. Greece (BMC, 2023)
Abstract Background Opioid addiction and overdose is a public health problem in the United States and is expected to remain with substance use increasing due to the COVID-19 pandemic. Communities that approach this issue through multi-sector partnerships experience more positive health outcomes. Understanding motivation for stakeholder engagement in these efforts is essential to successful adoption, implementation, and sustainability particularly in the shifting landscape of needs and resources. Methods A formative evaluation was conducted on the C.L.E.A.R. Program in Massachusetts, a state heavily impacted by the opioid epidemic. A stakeholder power analysis identified appropriate stakeholders for the study (n = 9). The Consolidated Framework for Implementation Research (CFIR) guided data collection and analysis. Surveys (n = 8) examined perception and attitudes on the program; motivations and communication for engagement; and, benefits and barriers to collaboration. Stakeholder interviews (n = 6) explored the quantitative findings in more detail. Surveys were analyzed using descriptive statistics and a content analysis with deductive approach was conducted for stakeholder interviews. The Diffusion of Innovation (DOI) Theory guided recommendations for communications to engage stakeholders. Results Agencies represented a range of sectors and the majority (n = 5) were familiar with the C.L.E.A.R. Program. Despite the many strengths of the program and existing collaboration, based on the coding densities of each CFIR construct stakeholders identified crucial gaps in the services the program provided and noted that the overall infrastructure of the program could be enhanced. Opportunities for strategic communication to address the stages of DOI align with the gaps identified in the CFIR domains to result in increased agency collaboration and expansion of services into the surrounding communities to ensure sustainability of the C.L.E.A.R. Program. Conclusions This study explored factors necessary for ongoing multi-sector collaboration and sustainability of an existing community-based program especially given the changing context from COVID-19. Findings informed both program revisions and communication strategies to promote the program to new and existing collaborating agencies and the community served, and identify effective communication approaches across sectors. This is essential for successful implementation and sustainability of the program, especially as it is adapted and expanded to address post-pandemic times. Trial registration This study does not report results of a health care intervention on human participants, however it was reviewed and determined an exempt study with the Boston University Institutional Review Board (IRB #H-42107).